Solar thermoelectric power generation in Cyprus: selection of the best system - Kalogirou, Soteris A. (My University, 2013)
Cyprus is planning to develop in the next few years one solar thermal power plant with a capacity of about 50 MW. Therefore, in this paper solar power systems are analyzed with respect to their technical characteristics, the cost of electricity produced and the land area required. The latter is very important for Cyprus as seaside areas are very expensive. Such a solar power station however should be located near the sea close to an existing power station. An additional reason is that such a solar plant can be combined with solar desalination to produce fresh water from seawater which is also a precious commodity for Cyprus. Based mainly on their industrial maturity and the advantages mentioned in this paper, the parabolic trough system seems to be to best one to apply. From a preliminary investigation of the various possible areas the author believes that the Vasilikos area near to the existing Vasilikos power station is the most suitable for such a system to be installed
Keywords: Parabolic trough collector; Central receiver system; Parabolic dish; Thermal storage